2018
DOI: 10.1371/journal.pone.0191384
|View full text |Cite|
|
Sign up to set email alerts
|

Hospitalizations due to unintentional transport injuries among Aboriginal population of British Columbia, Canada: Incidence, changes over time and ecological analysis of risk markers

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Transport injuries around the world often result in significant physical and psychological impairments and reduced quality of life [ 1 , 2 ]. Every year, road traffic accidents cost most countries in excess of 3% of their gross domestic product (GDP), and between 20 and 50 million people suffer non-fatal injuries, with many incurring a consequent disability [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Transport injuries around the world often result in significant physical and psychological impairments and reduced quality of life [ 1 , 2 ]. Every year, road traffic accidents cost most countries in excess of 3% of their gross domestic product (GDP), and between 20 and 50 million people suffer non-fatal injuries, with many incurring a consequent disability [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…This high rate extends into childhood and youth, where the risk of death due to suicide or homicide has been found to be 6.6 and 5.1 times higher among Indigenous children (Harrop et al 2007). Research in British Columbia has also indicated a high burden among Indigenous groups indicated by higher rates of hospitalization for injuries, with particularly high rates for intentional injuries (Brussoni et al 2016;George et al 2017;Jin et al 2015;Brussoni et al 2018). In the same line, compared with non-Indigenous peoples, injury-related mortality risk ratios were 2.65 and 1.89 among Métis males and females, respectively (Tjepkema et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In the same line, compared with non-Indigenous peoples, injury-related mortality risk ratios were 2.65 and 1.89 among Métis males and females, respectively (Tjepkema et al 2009). Possible factors contributing to a high incidence of injury in Indigenous peoples include isolated residence, the physical environment, crowded and dilapidated housing conditions, lifestyle, education, occupational risk, and poor social and economic conditions (Health Canada 2001;George et al 2017;Brussoni et al 2018;Brussoni et al 2015;Jin et al 2017;George et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 More recently, a study in British Columbia found that Aboriginal people were 1.89 times more likely to experience transportrelated injury between 1991 and 2010 than the general BC population. 3 Disparities in health status as well as in Aboriginal populations' access to health care and in the quality of the care available to them have also been well documented. Traumatic spinal cord injury (TSCI) is a particularly devastating type of trauma, requiring substantial acute and chronic care.…”
mentioning
confidence: 99%